A Newton-Raphson method based on eigenvalue sensitivities to improve harmonic voltage performance. - Varricchio, S.L (IEEE Transactions on power delivery)
This paper describes a Newton-Raphson method that accurately shifts a set of electrical network poles and transfer function zeros to more suitable locations in the complex plane to improve the harmonic voltage performance of a system. The descriptor system approach is used for the computer modeling of electrical networks of any topology and their subsequent modal analysis. The pole and/or zero shifts are carried out by appropriate changes in the system elements (e.g., capacitor and/or reactor banks). Eigenvalue sensitivity coefficients are used to help determine those element changes that are the most cost-effective and to compute the Jacobian elements for the Newton method. These changes may be carried out without impacting the system operating point. Results are presented for a realistic system model in order to show the potential applications of the method.